Intraductal papillary mucinous neoplasm of the biliary tract in the caudate lobe of the liver: a case report and literature review - Zhu, Xunhao; Ni, Qingqiang; Wang, Qianchang; Ma, Chaoqun; Yang, Faji; Gao, Hengjun; Zhu, Huaqiang; Zhou, Xu; Chang, Hong; Lu, Jun; Liu, Fangfeng (Frontiers in Oncology, 2023)
An intraductal papillary mucinous neoplasm of the biliary tract (BT-IPMN) in the caudate lobe of the liver is a rare tumor originating from the bile duct. Approximately 40% of the intraductal papillary neoplasms of the biliary tract (IPNB) secrete mucus and can grow in the intrahepatic or extrahepatic bile ducts. A 65-year-old woman presented with recurrent episodes of upper right pain. She developed her first episode 8 years ago, which resolved spontaneously. The frequency of symptoms has increased in the last 2 years. She underwent laparoscopic hepatectomy and choledochal exploration and was pathologically diagnosed with a rare BT-IPMN of the caudate lobe after admission. Here, we review studies on IPNB cases and systematically describe the pathological type, diagnosis, and treatment of IPNB to provide a valuable reference for hepatobiliary surgeons in the diagnosis and treatment of this disease.